Pengaruh Begadang Terhadap Kesehatan Tubuh dan Mental - Aisha Aulia; Susan Kladia Sianturi; Fypi Aldena Br Ginting; Ilham Pratama Siregar; Irwan Sigalingging; Josua Tarihoran; Roma Doni Siregar; Nimrot Manalu; Miftahul Ihsan; Andes Martua Harahap (Jurnal Sains Farmasi Dan Kesehatan, 2025)
In this fast-paced modern era, staying up late or nocturnal habits have become common among modern society, especially among students and workers. Although often seen as a way to complete tasks or socialize, staying up late can have significant negative impacts on physical and mental health. This study aims to identify the effects of staying up late on bodily and mental health and to provide recommendations for addressing this issue. The results indicate that staying up late can lead to fatigue, metabolic disturbances, and an increased risk of chronic diseases such as diabetes and heart disease. Additionally, lack of sleep is also associated with heightened levels of stress, anxiety, and decreased cognitive performance. To mitigate the negative effects of staying up late, it is recommended that individuals establish a consistent sleep schedule, avoid caffeine consumption before bedtime, and create a comfortable sleep environment. By paying attention to sleep quality, individuals can enhance their overall physical and mental health. This journal aims to examine the influence of staying up late on bodily and mental health and to provide recommendations for addressing this issue. By understanding the consequences of staying up late, it is hoped that individuals can be more prudent in managing their sleep time.